Discurso da criatividade: lógicas de produção, convocações para o consumo e gestão de si - Oliveira, Adriana Lima de (2016)
This paper aims to make a discourse analysis of creativity and its call for strategies both for the consumer and the management of himself intensely present in communicational processes of the contemporary society. Considering the changes in the political and economic scenario of mature capitalism and the consequent intensification of relations and exchanges in a market which appears increasingly flexible and fluid, the discourses of creativity and its visibility systems can be understood as biopolitical calls? Based on this questioning, we have investigated how the logicof these discourses is produced in a context that promotes creativity as an economic and social asset, for we have hypothesized that the economic discourse [expressible], classifies and represents creativity [object] and the creative person [subject] throgh whom this discourse is materialized on the market [visible] under a neoliberal perspective. So from this new status [being creative], the subject is able to find new ways of grouping, now has a creative [qualified]capital [knowledge]. To do so, we have elected government discourse as an example for this analysis and theoretical affiliation from the concepts of discourse and biopolitics proposed by Michel Foucault, linked to communication studies and consumption. Faced with this project, three analytical lenses have been mobilized: discourse, the device and governmentality. Presently, capitalism, which places 'knowledge' in the center of the production process, people with ideas [people who own ideas] are considered to be more powerful than those operating machines, and in many cases even more than those who have machines. But that does not mean all are included. Such an ideal creative society, in which in which hierarchy was gone and everyone was able to cooperate, must be questioned once it would envolve all meanings for inclusion as something because it takes the sense of the term inclusion as something hegemonic, universal and unproblematic.